Building a model for evaluating the efficiency of circular transformations in the context of technology transfer - Prokhorova, Viktoriia; Shkurenko, Olga; Kravchenko, Olha; Miahkykh, Iryna; Dalyk, Volodymyr; Kostiuk, Olha; Makovoz, Olena (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the process of circular transformations in the context of technology transfer. It has been proven that circular transformations in the context of technology transfer are a new challenge in the global directions of harmonization of economic processes. The relevance of the study is determined by the fact that the development of technologies, in particular "green" technologies under modern conditions has become a catalyst for changes in production, consumption, and management of resources, which contributes to the achievement of the goals of sustainable development of enterprises. This involves focusing on the formation and support of social integration of the production sector and society, reducing emissions into the environment, and ensuring the balanced development of business entities at different levels of management. The characteristics of the level of circular transformations in the countries of the world were studied. The relationship between technology transfer and circular transformations was established through indicators of the degree of greening of the economy. A SWOT analysis of circular transformations was conducted to identify key opportunities and threats that would affect the business environment. A model for evaluating the effectiveness of circular transformations has been built. Based on the proposed model, the GDP change forecast for the EU countries for 2023–2027 was calculated. Carbon dioxide emission trends were predicted under optimistic and pessimistic scenarios, which made it possible to justify the need to transition to a carbon-neutral model of economic development and the feasibility of implementing "green" technologies. The transition to a new model of economic development will allow for optimal management of depleted resources, wider use of resource-saving technologies and will reduce pressure on the environment